2010
DOI: 10.1111/j.1470-6431.2010.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Does strategic involvement of mental health service users and carers in the planning, design and commissioning of mental health services lead to better outcomes?

Abstract: There is an assumption, explicit in the current government policy, that involvement of mental health service users and carers in the planning, design and commissioning of mental health services will lead to better outcomes. The aim of this study was to examine evidence from board-level participation of service users and carers that might support this assumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…It has also been suggested that the benefits of service user involvement may be limited to the specific service users who are involved. Results of a thematic analysis of documents from minutes of meetings of a board partnership with the involvement of service users suggested that while there were positive outcomes for the service users involved, their presence may have been largely symbolic …”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that the benefits of service user involvement may be limited to the specific service users who are involved. Results of a thematic analysis of documents from minutes of meetings of a board partnership with the involvement of service users suggested that while there were positive outcomes for the service users involved, their presence may have been largely symbolic …”
Section: Findings and Discussionmentioning
confidence: 99%
“…A person-centred approach Valued characteristics of person-centred care found in the sample of literature were empathy and respectful listening, 7,23-30 treating service users with dignity and/or respect, 25,[31][32][33][34] being respected as an individual 7,25,31,33,35 and trust. 36 Building a therapeutic relationship was considered important by Greaves 24 and Borg et al 5 who suggested that this required interest in and awareness of the service user's daily life and difficulties.…”
Section: Key Attributes Of the Concept Of Service User Involvementmentioning
confidence: 99%
“…203,204 There is evidence of the political nature of some commissioning and procurement decisions and the impact of power on the resolution of conflicts between the preferences of different actors. 198,[206][207][208]484 There is also evidence of the use of sense-making behaviours, persuasion rather than power, to influence commissioning decisions. 199 l Evidence on selection and contracting in the NHS explicitly acknowledges the relevance of the economics of contracting literature.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the political character of decision-making processes in NHS commissioning and procurement has been provided by a number of authors. Horrocks et al 206 and Martin 207 look at the involvement of patient groups and members of the public in commissioning decisions. They conclude that the power of these actors to have a meaningful influence on decisions is highly contingent on factors such as decision scope and the coherence of a group's 'voice' on the matter under consideration.…”
Section: Round-upmentioning
confidence: 99%
“…Our findings resonate with those of Horrocks et al . 's in that the majority of time in meetings is taken by presentations from managers with limited opportunities for questions and debate. This practice is familiar to managers and some governors.…”
Section: Discussionmentioning
confidence: 99%